Measurement of the atmospheric neutrino flavour composition in Soudan 2 - Allison, W; Alner, G; Ayres, D; Barrett, W; Bode, C; Border, P; Brooks, C; Cobb, J; Cockerill, D; Cotton, R; Courant, H; DeMuth, D; et al. (1997)
The atmospheric neutrino flavour ratio measured using a 1.52 kton-year exposure of Soudan 2 is found to be 0.72 ± 0.19+0.05 -0.07 relative to the expected value from a Monte Carlo calculation. The possible background of interactions of neutrons and photons produced in muon interactions in the rock surrounding the detector has been investigated and is shown not to produce low values of the ratio.